Bio-products partially protect grapevine pruning wounds against infection of the trunk pathogen Lasiodiplodia theobromae - Escoriaza, Maria Georgina; Longone, Maria Valeria; Funes Pinter, Mariano Ivan; Uliarte, Ernesto Martin; Noli, Antonela (International Council on Grapevine Trunk Diseases (ICGTD), 2025)
Poster